Reliability Improvement Process Case Study: PT HMS Tbk - Putri, Sylvania; Utama, Akbar Adhi (Penerbit Goodwood, 2024)
Purpose: This study investigates the impact of unplanned and planned downtimes on PR (Production Reliability) performance in the tobacco industry, focusing on a company facing challenges due to COVID-19. Method: A mixed-method approach is employed, combining quantitative data analysis of production lines (Q1 2024) with qualitative interviews. Root cause analysis (Current Reality Tree) and prioritization (Analytical Hierarchy Process) are used to identify and evaluate solutions. Results: The research reveals maintenance focus on critical parts only and untested new materials as key contributors to low PR. Conclusions: Improving Process Reliability at PT HMS requires a dual focus on minimizing unplanned disruptions through predictive maintenance and structured response strategies, while also optimizing planned maintenance to reduce its operational impact. Implementing a comprehensive maintenance framework and validating new materials through rigorous testing will ensure smoother production, fewer disruptions, and enhanced overall performance. Limitations: The study focuses on one company during a specific timeframe. Contributions: This research proposes a framework for improving PR by recommending a comprehensive maintenance plan, thorough material testing, and an implementation plan based on the PDCA cycle. This is expected to lead to enhanced PR, reduced downtimes, and improved operational efficiency.